Neuroimmunomodulation by regional and general anaesthesia - Šakić Zdravčević, Kata (Array, 2009)
This review presents the detailed immunological impact of neural variables, including stress, on specific cellular and molecular events that that take place over the full (time course) duration of autoimmune, inflammatory, allergic and infectious diseases. A comprehensive search of literature from major injury (serious traumatic injury and major burns) to major surgical procedures that often lead to severe immunosuppression, which contributes to delayed wound healing, infectious complications and, in some cases, to sepsis, the most common cause of late death after trauma.